Rejuvenating multiple true–false: Proposing fairer scoring methods - Thomas, Puthiaparampil T.; Md Mizanur, Rahman; Sabrina, Lukas; Nariman, Singmame; Shazrina, Ahmad Razali (Digital Perspective Sdn. Bhd., 2023)
Introduction: Multiple true–false tests (MTF) with penalty scoring consistently delivered low scores and many failures for over two decades in our medical faculty. This issue remained unaddressed, as the overall student performance was redeemed by other assessments like Best Answer Questions and Modified Essay Questions. The post-test item analyses revealed that there were several items with unacceptable difficulty index and discrimination index, many omissions, and that the false options performed worse than the true options in the difficulty index but better in the discrimination index. This study aimed to evaluate some final professional examination MTF papers to propose possible remedial measures. Materials and Methods: We examined 5 years’ final professional examination MTF results, their item analysis, the student performance in true and false items and failure rates.We explored the impact of excluding the flawed questions post-test based on item analysis and redoing the scores. We also explored the effect of removing the penalty scoring and recalculating the scores. Results: The two new scoring methods, such as postweeding recalculation and no-penalty proportionate scoring, showed remarkable improvement in scores and also reduced the failure rates significantly compared to the penalty-scoring model. Conclusion: We propose two new scoring methods for MTF, which would be fairer to the students and would have the prospect of rejuvenating MTF tests.